Charge jornalística: estudo do discurso chargístico da Folha de S.Paulo veiculado no período da crise deflagrada pelo Primeiro Comando da Capital (PCC) - Lopes, Luís Fernando (2008)
A political cartoon both as text and discursive genre inserted into the printed media can mobilize in its textualization more than one language at the same time: verbal language (the written word) and other nonverbal languages (drawings, colors, shapes and the diagrammatical combinatory arrangement of all these elements). In that sense, this research aims at analysing the articulation of syncretic verbal language and visual language of political cartoons published by a reputable mass communication vehicle, to examine the textualization process implied in the political cartoons as one more opinion text present in printed newspaper, thus contributing to understanding its sense effects. For that proposition, the newspaper Folha de S.Paulo was used as a corpus (especially its political cartoons printed on page A2 entitled Opinion which had as their core theme the public security crisis that burst in May, 2006 with the attacks carried out by the Primeiro Comando da Capital PCC (the Capital s First Command) showing the discursive relationships interacting in the construction of sense as to the cartoon texts published in that printed media vehicle. This work also has the intention to form a important historical register with all political cartoons that were published and related to the public security crisis that burst in May, 2006 with the attacks carried out by the PCC